A “política na ordem”: perfis de lideranças e redes nas eleições da OAB/MA (1932-2022) - MEIRELES, Samário José Lima (2022)
This research analyzes the standards and selection processes of political leaders of the Maranhão section of the Brazilian Bar Association (OAB/MA), in the period between 1932 and 2022. The investigation focused on the dynamics of the elections, in which they were chosen the directors of the entity. In the operationalization of the study, it was sought to apprehend the chains of leaders-followers that competed within the scope of the institution, evidencing the flows of entries, exits, approximations and distances. In order to do so, the profiles of the main protagonists who competed and exercised the leadership positions of the OAB/MA were traced, as well as the cliques of leaders that were formed in these clashes and the cleavages built by means of constant realignments in the reconstituted alliances were located. Therefore, in the first place, the resources accumulated by the agents that stood out in these disputes were observed. Secondly, the networks of relationships (through the use of the Ucinet and Netdraw programs) constituted and activated due to the occupation of positions of power in the entity were identified. Thirdly, we also sought to reveal the social bases of more or less ephemeral interconnections, links and bonds. The purpose is to demonstrate how, over the course of 90 years, three segments of the elite of “bachelors” in law in Maranhão took turns in command of the OAB/MA, firstly as members of the “political elite” (1932/1973), then, participants of a “legal elite” (1973/2003), and, finally, members of the “private law elite” (2004/2022), always activating resources and interpersonal coalitions that cross different domains of the space of power in the State.